TOPSIS Method Application in Choosing The Most-Sale POS Cashier Machine Stuffs and Tools in PT. Mahadana Wikasita - Handayani, Rani Irma; Normah, Normah; Wironoto, Deni (Politeknik Ganesha Medan, 2021)
PT. Mahadana Wikasita is a company engaged in the sale of machine goods and pos cashier tools. In order to face business competition there are some problems that often arise regarding the sale of goods. PT. Mahadana Wikasita is lacking in monitoring the goods sold, what items consumers need and the storage of data is less effective, so the company can not determine exactly which goods to buy. Therefore, a decision support system is needed that can help solve this problem. In this research, the decision support system used is by Techinique for Order Reference by Similarity to Ideal Solution (TOPSIS) which consists of seven stages using several criteria such as price, type, quality and customer interest. In the test results calculated using the Method For Order Preference bySimiliarity to Ideal Solution (TOPSIS) it can be concluded that the highest value is kios Pakmo mobile cashier application package with a value of 0.920, can be interpreted as the best selling item for one year.